Divulgação do relato integrado, captação de recursos e valor de empresas do setor de energia elétrica - Oliveira, Palloma Rossany Maciel Rodrigues (2024)
Integrated Reporting (IR) aims to promote integrated thinking within organizations to provide more concise information that enables more efficient capital allocation. Several studies, carried out in a national and international context, have evaluated whether the disclosure of IR is related to better economic and financial results. However, an identified gap refers to the benefits evidenced by the disclosure of IR to the main users of accounting information, investors and creditors, in the Electric Energy sector. That said, this research had the general objective of identifying relationships between the dissemination of the Integrated Report, fundraising and value generation in companies in the electricity sector in Brazil. To meet the objective, the relationship between IR (disclosure and readability) and the variables: degree of financial leverage (GAF), credit ratings, public offering of shares (IPO and Follow-on) and the value of companies, whose proxy used was Tobin's Q. With a sample made up of companies in the electrical energy sector listed on B3, a period of 10 years was analyzed, covering the first IR publications in Brazil after the pilot project in Brazil (2013 to 2022). Multiple linear regression and binary logistic statistical tests were carried out, in which relationships were identified between the disclosure of the IR, the public offering of shares and the company's value. The results demonstrate that IR adds value from the point of view of investors, who provide capital to organizations, both in the value of shares and in fundraising via IPO and Follow-on. The variables GAF and Credit Ratings did not show a statistically significant relationship with IR. No significant relationships were also identified between readability and the variables studied (since none were related to readability). The study adds evidence on the benefits of IR disclosure from the investor's perspective in the Brazilian market, where the reporting of socioenvironmental information is carried out on a discretionary basis.